Controllable synthesis of alumina nanofibers with tunable crystal phases via a facile and cost-effective dealloying process - Qianwen Sun; Zhenying Huang; Wenqiang Hu; Haozheng Han; Weici Zhuang; Xue Li; Youbo Wu; Xinkang Li; Ziqiang Zhu; Yang Zhou (Journal of Advanced Ceramics)
Owing to their unique mechanical properties and excellent thermal and chemical stability, Al2O3 nanofibers are highly desirable for practical applications as functional and structural building blocks. However, the scalable production of Al2O3 nanofibers has always faced significant challenges, namely, high cost and complicated processes. This work explores a feasible and straightforward dealloying strategy for the batch synthesis of Al2O3 nanofibers. When a binary Al‒Li alloy is immersed in alcohol, the alkoxide nanofibers spontaneously grow following the mechanism of boundary strain energy minimization. The results indicate that by dissolving Li in Al‒Li alloys, the continuous exposure of a fresh Al surface renders the remaining unsaturated bonds of Al sufficiently reactive, providing the conditions for the subsequent reaction with alcohols and thus inducing the formation of alcohol‒aluminum compounds. These nanofibers were calcined in air to obtain monocrystalline α-Al2O3 and polycrystalline γ-Al2O3 nanofibers. We investigated the evolution of the alloy into nanofibers in dry ethanol and the influence of different Al‒Li alloy compositions and calcination temperatures on the crystal structure and morphology of the resulting Al2O3 nanofibers. The study revealed that γ-Al2O3 with diameters of approximately 50–80 nm and lengths of approximately 20–30 μm and α-Al2O3 with diameters of approximately 100–150 nm and lengths of approximately 15–20 μm were successfully prepared via this technique route. The approach reported in this study is anticipated to open new paths for the efficient and economical synthesis of advanced metal oxide nanofibers and lay the foundation for their extensive application in current industrial sectors.